2016
DOI: 10.4236/oalib.1103156
|View full text |Cite
|
Sign up to set email alerts
|

Issues Affecting the Adoption and Usage of Mobile Instant Messaging in Semi-Rural Public Schools of South Africa for Learning

Abstract: Mobile instant messaging technologies have become popular among the youth, they predominantly use it to socialise, communicate and share information anywhere and anytime and it provides the platform which learners can use for learning from specialists across the world. This study was conducted in semi-rural schools in the Vhembe District in Limpopo Province of South Africa. Diffusion of innovation theory was used to determine factors that could promote the adoption of mobile instant messaging for learning math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The reason why this hypothesis is supported is because the better the relative advantages that electronic money has, the faster customers will adopt electronic money. This hypothesis is supported in accordance with previous research where the advantages are relatively related to adoption (Harridge et al, 2008;Wei & Ismail, 2009;Thambiah et al, 2010;Moghavveni et al, 2012;Ozuru & Opara, 2014;Girsang & Hatammimi, 2014;Mashau, 2016;Niranjan et al, 2016;Ilin et al, 2017;Ramli et al, 2017;Chavali & Kumar, 2018) which states that relative excellence is an antecedent of adoption and that both constructs must positively associate with each other.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The reason why this hypothesis is supported is because the better the relative advantages that electronic money has, the faster customers will adopt electronic money. This hypothesis is supported in accordance with previous research where the advantages are relatively related to adoption (Harridge et al, 2008;Wei & Ismail, 2009;Thambiah et al, 2010;Moghavveni et al, 2012;Ozuru & Opara, 2014;Girsang & Hatammimi, 2014;Mashau, 2016;Niranjan et al, 2016;Ilin et al, 2017;Ramli et al, 2017;Chavali & Kumar, 2018) which states that relative excellence is an antecedent of adoption and that both constructs must positively associate with each other.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research shows that relative advantage influences internet-based adoption of information and communication technology (Girsang & Hatammimi, 2014), adoption of cellular banking, adoption of electronic banking services (Ozuru & Opara, 2014), adoption of retail banking services (Thambiah et al, 2010), information adoption of technological innovation (Moghavvemi et al, 2012), adoption of brick installation technology (Ramli et al, 2017), cellular direct message adoption (Mashau, 2016), technology adoption between businesses (Wei & Ismail, 2009), adoption of enterprise resource planning (Ilin et al, 2017), adoption of electronic money (Niranjan et al, 2016). Thus, the following hypothesis is as follow: H1: There is a positive relationship between relative excellence and the adoption of electronic money.…”
Section: Hypothesis Development Relative Advantage and E-money Adoptionmentioning
confidence: 99%
“…were not trained and they found it difficult to use online LMS. This finding is supported byMashau (2016) who suggests that training is important in the technology usage and will influence the adoption of the new innovation. Furthermore, most respondents were unable to use online LMS for learning because of intermittent internet connectivity problems.…”
mentioning
confidence: 74%
“…They claimed that they could study wherever they were. Indeed, previous studies have suggested that mobile learning enables students to study at any time without being confined within four walls (Habes et al, 2018;Mashau, 2016;Sarwar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%